Sosialisasi Gerakan Masyarakat Hidup Sehat di Desa Bulutellue Kabupaten Sinjai Provinsi Sulawesi Selatan - Abdul Rahman; Firdaus W. Suhaeb; Najamuddin Najamuddin (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this community service activity is to provide an understanding to the community about the need to implement the Healthy Living Community Movement (Germas) by keeping the environment clean and consuming good and healthy food and drinks. The method used is the method of socialization, education, and community performance through community service activities. The results of the dedication show that this activity received the attention and support of the government and the community of Bulutellue Village. Based on observations at the community service location, the community has adopted a healthy lifestyle as an implementation of Germas.